Cover Feature: Weinreb Amide, Ketone and Amine as Potential and Competitive Secondary Molecular Stations for Dibenzo‐[24]Crown‐8 in [2]Rotaxane Molecular Shuttles (Chem. Eur. J. 70/2021). Issue 70 (3rd December 2021) - Gauthier, Maxime; Coutrot, Frédéric
Abstract : A chemical way to bistable molecular shuttles that hold a combination of amine, Weinreb amide and/or ketone as secondary stations for dibenzo‐[24]crown‐8 (DB24C8) is reported. Ketone and amine moieties have similar affinity for DB24C8 that is better than the Weinreb amide has. Hydrogen bonds between DB24C8 and an unhindered axle usually favor a co ‐conformation; unless steric restrictions, hence the constrained co ‐conformation, impose a predominance of alternative and unexpected even weaker H‐bonds. More information can be found in the Research Article by M. Gauthier and F. Coutrot (DOI: 10.1002/chem.202103805 ).